At the Way of Cognition of Anthropocentric Existence of Language: Ukrainian Sociopsycholinguistics of the End of ХХ – the Beginning of ХХІ Century - Філон, Микола Іванович; Галунова, Наталія Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is devoted to the actual for contemporary linguistics problem of origination of a new branch of science at the border of the already existing ones – to sociopsycholinguistics. The analysis of Ukrainian psycholinguistic and sociolinguistic researches demonstrates affinity of their problems, objects, subjects, and the usage of the same methods. The problems, the object, the subject, the methods and perspective research guidelines of sociopsycholinguistics are characterized in the article. Importance and heuristic significance of sociopsycholinguistics for formation of a scientific-research image of the language in its social and anthropocentric dimensions are emphasised.